SPIRITUALITAS PEMBINA SEKAMI PAROKI ST. GREGORIUS AGUNG OELETA KEUSKUPAN AGUNG KUPANG - Oetpah, Dorince (Pastoralia Jurnal Penelitian Dosen, 2021)
The research entitled "Spirituality of SEKAMI Trustees of St. Gregorius Agung Kupang” was written with the intention of exploring the extent to which the SEKAMI Trustees of St. Gregory Agung Oeleta of the Kupang Archdiocese understands their spirituality. This is because the majority of coaches are not actively involved in SEKAMI activities which are carried out both during the normal coaching period and during the Covid-19 pandemic. This research is considered important because after all SEKAMI coaches are figures who have quite a big influence on the growth and development of children's faith apart from parents and teachers. This research uses qualitative methods. And the data collection process will use observation and interview techniques. The informants in this interview were six SEKAMI supervisors.